Intermediary Management and Employee Corporate Culture Identification Mediation and Mediation Effect Verification - Liu, Mingji; Li, Jinyao; Xiong, Tianlang; Liu, Tong; Chen, Min (Frontiers in Psychology, 2021)
This exploration is mainly to study the role of corporate culture accepted by employees in enterprise development and its impact on employees themselves. First, the influence of employee participation, cross-cultural management and corporate culture on the enterprise is realized through the relevant literature. Then, investigation and analysis are carried out with American I Industrial Group as the research object, so as to determine the impact of cross-cultural management on mergers and acquisitions and organizational performance. The results show that the total impact of trust on reuse is 0.264 before mergers and acquisitions, the difference is not statistically significant, and so is the overall impact of mergers and acquisitions. This means that there is no correlation between trust and reuse. However, when the merger is done, the total effect of trust on reuse rises to 1.594, indicating that the difference and the total effect are statistically significant. The data calculation and analysis for the direct impact of trust on reuse and the indirect impact of trust on reuse are 0.667 and 0.926, respectively, which means that the difference is statistically significant. This proves the role of satisfaction in the impact of trust on reuse once mergers and acquisitions is completed. Therefore, in the process of mergers and acquisitions in the future, enterprises must consider the different cultures of employees and company locations and employee participation, which will further affect the organizational performance of enterprises.